An analysis of complaints about hospital care in the Republic of Ireland. (12th May 2022) - O'dowd, Emily; Lydon, SinÉad; Lambe, Kathryn; Vellinga, Akke; Rudland, Chris; Ahern, Elaine; Hilton, Aoife; Ward, Marie E; Kane, Maria; Reader, Tom; Gillespie, Alex; Vaughan, David; et al.
Abstract: Background: Patients and family members make complaints about their hospital care in order to express their dissatisfaction with the care received and prompt quality improvement. Increasingly, it is being understood that these complaints could serve as important data on how to improve care if analysed using a standardized tool. The use of the Healthcare Complaints Analysis Tool (HCAT) for this purpose has emerged internationally for quality and safety improvement. Previous work has identified hot spots (areas in care where harm occurs frequently) and blind spots (areas in care that are difficult for staff members to observe) from complaints analysis. This study aimed to (i) apply the HCAT to a sample of complaints about hospital care in the Republic of Ireland (RoI) to identify hot spots and blind spots in care and (ii) compare the findings of this analysis to a previously published study on hospital complaints in the UK. Methods: A sample of complaints was taken from 16 hospitals in the RoI in Quarter 4 of 2019 ( n =  641). These complaints were coded using the HCAT to classify complaints by domain, category, severity, stage of care and harm. Chi-squared tests were used to identify hot spots, and logistic regression was used to identify blind spots. The findings of this study were compared to a previously published UK study that used HCAT to identify hot spots and blind spots. Results: Hot spots were identified in Irish hospital complaints while patients were receiving care on the ward, during initial examination and diagnosis, and while they were undergoing operations or procedures. This aligned with hot spots identified in the UK study. Blind spots were found for systemic problems, where patients experience multiple issues across their care. Conclusions: Hot spots and blind spots for patient harm can be identified in hospital care using the HCAT analysis. These in turn could be used to inform improvement interventions, and direct stakeholders to areas that require urgent attention. This study also highlights the promise of the HCAT for use across different healthcare systems, with similar results emerging from the RoI and the UK.